Pengaruh Promosi Online Dan Persepsi Harga Terhadap Keputusan Pembelian Pada Rubylicious Di Kota Malang (Studi Pada Mahasiswa Prodi Manajemen FEB Universitas Islam Malang Angkatan 2018-2020) - Lismayani Lismayani; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to find out and analyze whether online promotion and price perception affect purchasing decisions at Rubylicious for 2018-2020 FEB Management Study Program students, Islamic University of Malang. This type of research is explanatory research or explanatory research using a quantitative approach. The theory used is Malhotra theory with the number of samples in this study there are 21 question items. So the number of samples taken in this study were 105 samples (21 question items x 5) which were Rubylicious online shop consumers. Sampling technique used in this research is by using purposive sampling technique. Analysis of the data used is descriptive statistics and multiple linear regression analysis. The results of this study indicate that simultaneously the independent variables Online Promotion and Price Perception have a significant effect on the dependent variable, namely Purchase Decision. Partially, it can be seen from the t-test results which show that the Online Promotion variable has a significance level of 0.005 <0.05. While the price perception variable has a significance level of 0.000 <0.05. Based on these calculations, it can be concluded that partially Online Promotion and Price Perception have a significant influence on Purchase Decisions. Meanwhile, descriptive analysis shows that by doing online promotions well, it will increase someone's interest in making purchasing decisions and also create price perceptions that are in accordance with the products offered. Keywords: Online Promotion, Price Perception, and Purchase Decision